2015
DOI: 10.3390/nu7042456
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Nutrition in Dementia: A Systematic Review

Abstract: The aim of this systematic review is to evaluate the role of enteral nutrition in dementia. The prevalence of dementia is predicted to rise worldwide partly due to an aging population. People with dementia may experience both cognitive and physical complications that impact on their nutritional intake. Malnutrition and weight loss in dementia correlates with cognitive decline and the progress of the disease. An intervention for long term eating difficulties is the provision of enteral nutrition through a Percu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 52 publications
(102 reference statements)
0
30
1
6
Order By: Relevance
“…In addition, there was no difference between enteral tube insertion in an earlier or a later stage in the course of the disease in relation to survival outcome 64. Two recent reviews of observational studies also acknowledged the lack of evidence to suggest a positive correlation between enteral tube feeding and survival 65 66. The risks of enteral feeding in patients with advanced dementia are related to procedural complications, postinsertion tube management (eg, blockages and dislodgements) and the tendency of cognitively impaired patients to interfere with the tube (eg, by pulling the tube out) 59…”
Section: Enteral Feeding In Alzheimer's Disease and Other Dementiasmentioning
confidence: 99%
“…In addition, there was no difference between enteral tube insertion in an earlier or a later stage in the course of the disease in relation to survival outcome 64. Two recent reviews of observational studies also acknowledged the lack of evidence to suggest a positive correlation between enteral tube feeding and survival 65 66. The risks of enteral feeding in patients with advanced dementia are related to procedural complications, postinsertion tube management (eg, blockages and dislodgements) and the tendency of cognitively impaired patients to interfere with the tube (eg, by pulling the tube out) 59…”
Section: Enteral Feeding In Alzheimer's Disease and Other Dementiasmentioning
confidence: 99%
“…For instance, dementia is a long-term condition that impacts on people’s cognitive and physical abilities which can affect their nutritional intake, leading to malnutrition [9]. Malnutrition in patients with dementia appears to correlate with cognitive decline and the progression of the disease.…”
mentioning
confidence: 99%
“…In a systematic review on the use of enteral nutrition in patients with advanced dementia, Finucance et al [10] did not find any improvements in the rates of aspiration, pressure sores and mortality and therefore concluded that enteral nutrition for patients with dementia should be discouraged [10]. In contrast, recent recommendations from the systematic review by Brooke and Ojo [9] challenged this position and instead suggested the need for a holistic assessment of patients with dementia requiring enteral nutrition and PEG tube placement. These assessments should include a diagnosis of patients—comorbidities, current stage of dementia, acute medical illness and its impact on nutritional status [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a systematic review of PEG feeding in patients with severe dementia found no improvement in survival and showed high complication rates 10. And these procedures carry a high risk of mortality in patients with severe disease and poor physical reserve 11121314…”
mentioning
confidence: 99%